Prevention and Control Strategies of Dengue Hemorrhagic Fever in Indonesia - Sunarsih Sunarsih; Tri Rizkiyanti Alwi; Andi Zuhra Ibrahim; Itha Puspita Sari; Masiti Masiti; Sy. Rugaiyah; Sri Handayani (PT. Anagata Sembagi Education, 2025)
Dengue Hemorrhagic Fever (DHF) is a significant public health issue in Indonesia, with incidence rates fluctuating every year. This study aims to identify and analyze the prevention and control strategies for DHF in Indonesia over the last five years (2019–2024) using a literature review method. The analyzed articles were selected based on inclusion criteria such as publications in Indonesian or English, published between 2019 and 2024, and directly discussing prevention or control strategies for DHF. The results show that strategies implemented in Indonesia include community-based approaches such as the 3M Plus movement, the use of innovative technologies like Wolbachia-infected mosquitoes, enhancement of surveillance systems, public education, and strengthening cross-sector coordination. Despite various efforts, challenges such as vector resistance, climate change, and lack of inter-agency synergy still hinder program effectiveness. Therefore, more integrated, evidence-based policies oriented toward community participation are needed to achieve optimal and sustainable DHF control.